Cosmic powers : the Saga anthology of far-away galaxies - Adams, John Joseph, 1976- (Saga Press, 2017)
"A collection of original, epic science fiction stories by some of today's best writers--for fans who want a little less science and a lot more action--and edited by two-time Hugo Award winner John Joseph Adams. Inspired by movies like The Guardians of the Galaxy and Star Wars, this anthology features brand-new stories from some of science fiction's best authors including Dan Abnett, Jack Campbell, Linda Nagata, Seanan McGuire, Alan Dean Foster, Charlie Jane Anders, Kameron Hurley, and many others"--